2020
DOI: 10.25159/1998-8125/6398
|View full text |Cite
|
Sign up to set email alerts
|

Talent Development Practices Predict the Employee Engagement of Human Resource Professionals

Abstract: There is little evidence to indicate the association between talent development practices and the employee engagement of human resource (HR) professionals. The aim of this study was to examine if talent development practices predict the employee engagement levels of HR professionals. The study was conducted by means of a quantitative survey research design based on a sample of 354 HR professionals. A stratified random sampling technique was applied and data were collected by means of the Survey Monkey internet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…Also, the studies by Bai and Liu (2018) and Liu et al (2017) corroborated the finding of the study that talent development had a significant positive impact on work engagement. However, the finding of the study was contrary to those of the studies by Lee and Eissenstat (2018) and Morethe et al (2020), who reported that talent development opportunities had no significant relationship with work engagement of employees. Nonetheless, with the finding of the study agreeing with those of most previous scholars, it can be affirmed that talent development strategies have a largely significant positive relationship with work engagement of non-teaching workforce.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Also, the studies by Bai and Liu (2018) and Liu et al (2017) corroborated the finding of the study that talent development had a significant positive impact on work engagement. However, the finding of the study was contrary to those of the studies by Lee and Eissenstat (2018) and Morethe et al (2020), who reported that talent development opportunities had no significant relationship with work engagement of employees. Nonetheless, with the finding of the study agreeing with those of most previous scholars, it can be affirmed that talent development strategies have a largely significant positive relationship with work engagement of non-teaching workforce.…”
Section: Discussioncontrasting
confidence: 99%
“…Talent development provides satisfaction to employees as it is regarded as a positive exchange, hence contributing to their development of work engagement (Lee & Eissenstat, 2018). Studies (Ajibola et al, 2019;Aybas & Acar, 2017;Bai & Liu, 2018;Lee & Eissenstat, 2018;LeVan, 2017;Morethe et al, 2020;Mugizi et al, 2020b;Pandita & Ray, 2018) examined the relationship between talent development and employee engagement. However, contrary to other scholars, Lee and Eissenstat (2018) and Morethe et al (2020) reported that talent development opportunities had no significant relationship with work engagement of employees.…”
Section: Talent Management Strategies and Work Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim and Koo (2017) found that LMX was directly related to job engagement but only indirectly related to organization engagement through job engagement. Morethe et al (2020) found that talent development practices were significantly related to organization engagement but not related to job engagement. Sharma and Raina (2013) found that while job content and benefits were related to job engagement, job content, benefits and objectivity were related to organization engagement.…”
Section: Organization Engagement Compared To Job Engagementmentioning
confidence: 86%
“…Relationship between organization engagement and job engagement. With respect to the relationship between organization engagement and job engagement, most studies found a moderate correlation between them (Aghaz and Tarighian, 2016;Agrawal, 2015;Altarawneh, 2012, 2014;Andrew and Sofian, 2012;Bhasin et al, 2019;Byrne and MacDonagh, 2017;Farndale et al, 2014;Ghosh et al, 2014;Jain and Ansari, 2018;Kim and Koo, 2017;Morethe et al, 2020;Musgrove et al, 2014), although several studies found a correlation above 0.70 (Lee et al, 2014;Qi et al, 2018;Sharma and Raina, 2013;Suhartanto and Brien, 2018). Furthermore, most studies reported higher scores for job engagement than organization engagement (Aghaz and Tarighian, 2016;Akingbola and van den Berg, 2019;Altarawneh, 2012, 2014;Bhasin et al, 2019;Byrne and MacDonagh, 2017;Farndale, 2017;Farndale et al, 2014;Ghosh et al, 2014;Jain and Ansari, 2018;Lee et al, 2014;Morethe et al, 2020;Musgrove et al, 2014;Sharma and Raina, 2013;€ Unal and Turgut, 2015), although a few studies found higher scores for organization engagement (Agrawal, 2015;Andrew and Sofian, 2012;Malinen and Harju, 2017;Shah and Beh, 2016).…”
Section: Organization Engagement Compared To Job Engagementmentioning
confidence: 99%